Ailanthone as a novel AKT1 inhibitor that induces mitochondrial apoptosis and exerts anti-tumor activity in cervical cancer - Huang, Shaofeng; Song, Yanlun; Zhao, Yun; Zhang, Xin; Jiao, Yannan; Zhang, Jin; Huang, Yuehua; Wang, Junli; Qin, Haimei; Yang, Fenglian; Wang, Rong (Translational Cancer Research; Online First, 2026)
As a significant global burden on women's health, cervical cancer necessitates the exploration of novel therapeutic strategies driven by the limitations inherent in the current treatment options. Ailanthone (AIL), a natural compound derived from Ailanthus altissima, has significant inhibitory effects against various tumor types. However, its function in cervical cancer and associated molecular mechanisms are yet to be elucidated.